An Experimental Investigation into the Effect of Flap Angles for a Piezo-Driven Wing. Issue 1 (March 2013) - DeLuca, Anthony M.; Reeder, Mark F.; Cobb, Richard G.
This article presents a comparison of results from six degree of freedom force and moment measurements and Particle Image Velocimetry (PIV) data taken on the Air Force Institute of Technology's (AFIT) piezoelectrically actuated, biomimetically designed Hawkmoth, Manduca Sexta, class engineered wing, at varying amplitudes and flapping frequencies, for both trimmed and asymmetric flapping conditions to assess control moment changes. To preserve test specimen integrity, the wing was driven at a voltage amplitude 50% below the maximum necessary to achieve the maximal Hawkmoth total stroke angle. 86° and 65° stroke angles were achieved for the trimmed and asymmetric tests respectively. Flapping tests were performed at system structural resonance, and at ±10% off system resonance at a single amplitude, and PZT power consumption was calculated for each test condition. Two-dimensional PIV visualization measurements were taken transverse to the wing planform, recorded at the mid-span, for a single frequency and amplitude setting, for both trimmed and asymmetric flapping to correlate with the 6-DoF balance data. Linear velocity data was extracted from the 2-D PIV imagery at ± 1/2 and ±1 chord locations above and below the wing, and the mean velocities were calculated for four separate wing phases during the flap cycle. The mean forces developed during a flap cycle were approximated using a modification of the Rankine-Froude axial actuator disk model to calculate the transport of momentum flux as a measure of vertical thrust produced during a static hover flight condition. Values of vertical force calculated from the 2-D PIV measurements were within 20% of the 6-DOF force balance experiments. Power calculations confirmed flapping at system resonance required less power than at off resonance frequencies, which is a critical finding necessary for future vehicle design considerations.